Endothelial Colony Forming Capacity is Related to C-Reactive Protein Levels in Healthy Subjects - Ciulla, Michele M; Giorgetti, Alessandra; Silvestris, Ilaria; Cortiana, Michela; Montelatici, Elisa; Paliotti, Roberta; Annoni, Giuseppe A; Fiore, Anna V.; Giordano, Rosaria; Marco, Federico D.; Magrini1, Fabio; Rebulla, Paolo; et al. (Current Neurovascular Research, 2006)
The majority of clinical studies on endothelial progenitor cells (EPCs) focuses on the role of these cells in cardiovascular diseases and no systematic studies exist regarding their variations in healthy subjects. In order to define the burden of angiogenesis in physiological conditions we assessed the frequency of peripheral blood endothelial colonies (PB-ECs) and their relation with other factors possibly involved in their function such as high-sensitivity C-reactive protein (hs-CRP), endothelial cell-specific mitogen factor (VEGF) and tissue inhibitor of metalloproteinases-1 (TIMP-1) in a highly selected healthy population. A PB sample was obtained from 37/47 healthy subjects (age 40.2±15.0yrs; M/F 15/22) without known cardiovascular risk factors. The serum level of hs-CRP, VEGF, TIMP-1, the frequency of PB-ECs by clonogenic assay, and the number of early EPCs and late EPCs by flow cytometry analysis were evaluated. PB-ECs were formed by 40.5% of studied subjects with a mean of 0.40±0.82 colonies/106 cells. The differences in the frequency of colony formation between genders were not statistically significant. The subjects with PB-ECs were characterized by higher values of hs-CRP, when compared with those not forming colonies, 0.276±0.230 vs 0.095±0.077 mg/l (p=0.003) respectively, and of VEGF, 328.3±162.9 vs 202.68±118.53 pg/ml (p=0.02). No significant differences were found in TIMP-1 values. The EPC clonogenic potential seems to be related to hs-CRP and VEGF levels even in healthy population supporting the concept that these mediators are involved in physiological ECs function.
Keywords: Endothelial progenitor cells